The Internalization of al-Hikam Values in the Moral Education Curriculum at Pesantren Tebuireng (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2023)
Al-Hikam, written by Ibn ‘Atha’illah al-Sakandari, is one of the classical Sufi works rich in moral and Islamic spiritual values. This study aims to analyze the process of internalizing the values of al-Hikam within the moral education curriculum at Pesantren Tebuireng. The research employs a qualitative method with a descriptive-analytical approach, using literature review, observation, and interviews with pesantren caregivers and educators as data collection techniques. The findings indicate that the core values of al-Hikam, such as sincerity, reliance on God (tawakkul), patience, humility, and awareness of human dependence on Allah, are systematically integrated into the moral education curriculum. The internalization of these values is implemented through the study of classical texts, the exemplary conduct of kiai and teachers, the habituation of religious practices, and the pesantren culture that emphasizes character building among students. The curriculum is not limited to cognitive aspects but also encompasses affective and practical dimensions, enabling the Sufi values of al-Hikam to shape students’ personalities toward noble character, moderation, and spiritual orientation. Thus, Pesantren Tebuireng presents a holistic model of moral education through the integration of classical Sufi teachings with the modern pesantren educational system.